Analysis of Actual Costs and INA-CBG Rates for Breast Cancer Care in Indonesian Hospitals: A Narrative Review - Hanum Nasiha; Dewi Purnamawati (Indonesian Health Journal, 2026)
Breast cancer is a global health challenge and a significant economic burden in Indonesia, given its high prevalence among women. This study aims to evaluate the gap between actual medical costs and INA-CBGs rates in breast cancer management to formulate policy recommendations for the sustainability of oncology services. The research was conducted through a narrative review of literature published in 2022–2026 from the Scopus, ProQuest, and Dimensions databases. The review of three selected articles confirmed the existence of a substantial disparity in costs, characterized by a consistent negative difference between actual hospital costs and JKN claim rates. The findings show that the largest cost component comes from cytostatic drugs at 62–69%, while radiotherapy services are reimbursed at only about 59–87% of actual costs. This discrepancy is further exacerbated by medical inflation and the increasing complexity of managing advanced cases. In conclusion, structural cost discrepancies threaten the financial stability of hospitals, necessitating a periodic revision of rates based on activity-based costing and the implementation of a carve-out policy for high-value oncology drugs to ensure sustainable service accessibility.